2013
DOI: 10.1152/ajpregu.00191.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory mechanism of the nucleus of the solitary tract involved in the control of cardiovascular, dipsogenic, hormonal, and renal responses to hyperosmolality

Abstract: The nucleus of the solitary tract (NTS) is the primary site of visceral afferents to the central nervous system. In the present study, we investigated the effects of lesions in the commissural portion of the NTS (commNTS) on the activity of vasopressinergic neurons in the hypothalamic paraventricular (PVN) and supraoptic (SON) nuclei, plasma vasopressin, arterial pressure, water intake, and sodium excretion in rats with plasma hyperosmolality produced by intragastric 2 M NaCl (2 ml/rat). Male Holtzman rats wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
24
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 52 publications
(105 reference statements)
8
24
1
Order By: Relevance
“…; Blanch et al . ). However, the combined antagonism of both glutamatergic and purinergic receptors in the cNTS did not affect the chemoreflex‐induced tachypnoea (Braga et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…; Blanch et al . ). However, the combined antagonism of both glutamatergic and purinergic receptors in the cNTS did not affect the chemoreflex‐induced tachypnoea (Braga et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Blanch et al . ). Neurones of the NTS are also part of the dorsal respiratory group involved in processing information arising from pulmonary stretch receptors and peripheral chemoreceptors (Bianchi et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A potential pathway from the ARN to SON has been suggested in earlier work (Ciriello et al, 2004; Fitch et al, 2000; Huang and Weiss, 1999). Others have proposed input to the SON from sodium loading in the vasculature or CNS (Blanch et al, 2013; Carlson et al, 1997; Moellenhoff et al, 1998; Morita et al, 1997; Rinaman et al, 1997). We suggest that sodium sensitive ENaCs in the renal pelvis increase ARN activity that ultimately reaches neurons in the SON and PVH which regulate vasopressin release (Day and Ciriello, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Many authors have reported activation of several sites including circumventricular organs after intravenous (Bisley et al, 1996; Ho et al, 2007), intragastric (Kobashi et al, 1993; Carlson and Osborn, 1998; Carlson et al, 1997; Blanch et al, 2013) intracerebroventricular (Moellenhoff et al, 1998), or intraportal vein administration (Morita et al, 1997). These typically include the NTS, AP, PBel, SON and PVH and have been ascribed to either direct increases in plasma or CSF osmolality or to activation of sodium receptors in the portal vein.…”
Section: Discussionmentioning
confidence: 99%